Microinjection moulded polyetheretherketone biomaterials as spinal implants: physico-chemical and mechanical characterisation. (19th December 2018) - Tuinea-Bobe, C L; Xia, H; Ryabenkova, Y; Sweeney, J; Coates, P D; Fei, G
Abstract: Polyetheretherketone (or PEEK) is a thermoplastic polymer known for its high plasticity and toughness and has been widely employed as a material for a variety of load-bearing medical devices ranging from trauma implants to interspinal spacers and femoral stems. While being inherently chemically inert and therefore biocompatible and having very short lived post-radiation free radicals, PEEK presents different mechanical properties depending on its degree of crystallinity. It can be processed via extrusion, injection or compression moulding. However, these techniques do not allow high precision control over the fine morphological structure that strongly influences mechanical properties. Microinjection moulding, in contrast, makes it possible to produce fine details of medical implants with high precision and accuracy. Another advantage of this method is the controlled production of the material with heterogeneous structure due to variations in crystallinity. Having stiffness in the middle of the sample different from that at the edges enables a structure that mimics the bone/cartilage parts of an implant. This paper reports on the manufacturing of PEEK components by microinjection moulding, and their characterisation by physico-chemical (XRD, SAXS, TEM, FTIR, POM) and mechanical (tensile testing) means, in order to assess the suitability of use for biomedical application, such as spinal implants. We discuss the influence of such parameters as mould temperatures, injection speeds and hold pressures on the crystallinity and mechanical properties of the material.